Geological control on aquifer storage and recovery (ASR) feasibility and efficiency in carbonate aquifers (Edwards aquifer and Floridan aquifer) - Simbo, Christophe Wakamya, author; Sutton, Sally, advisor; Sale, Tom, committee member; Ronayne, Michael, committee member; Ridley, John, committee member (Colorado State University. Libraries, 2024)
Aquifer storage and recovery (ASR) is increasingly being used to enhance freshwater security and sustainability. Though proven technology, ASR implementation and efficiency are mainly controlled by the aquifer system's geological characteristics. Aquifer or reservoir quality, aquifer geochemistry and heterogeneity, and ASR-induced stress exerted on aquifer systems affect the operation of ASR and, hence, ASR recovery feasibility and efficiency. This dissertation evaluates the feasibility of ASR operations in two major carbonate aquifers in the USA: the brackish portion of the Edwards aquifer and the Floridan aquifer. Aquifer matrix petrology and geochemistry, groundwater geochemistry, surface water geochemistry, and time series water chemistry coupled with numerical modeling with PHAST and Geochemists' Workbench (GWB), and analytical modeling were used to understand the aquifers and evaluate ASR optimization strategies. The Edwards Aquifer petrography provides insights into the aquifer texture, fabric, and aquifer/reservoir quality controlled by depositional and post-depositional processes. Though the development of porosity and permeability are likely controlled by the precursor texture of the aquifer matrix, diagenetic processes, mainly dolomitization together with fracturing and dissolution, may be the main agents affecting aquifer quality for ASR operation. Suitable aquifer zones for water storage are characterized by permeability likely controlled by intercrystalline, fracture, and vuggy porosity in dolomitic zones. Bulk aquifer geochemistry documents major and trace elements, with high MgO/CaO revealing extensive dolomitization preferentially located towards the middle of the Person and Kainer Formations, aquifer units within the Edwards aquifer system. The relatively higher content of SiO2, Al2O3, and, to some extent, K2O and TiO2 in confining layers points to a modest increase in clay minerals compared to aquifer sections. Clay minerals, together with compaction features observed in confining layer thin sections, potentially reduce confining layer permeability and porosity. However, high fracture porosity within the Regional Dense Member (RDM) confining layer separating both Edwards aquifer zones offers potential pathways connecting both zones. That these fractures may, in fact, be pathways is supported by changes in groundwater hydrochemistry in the non-targeted aquifer zone (Kainer) during the initial ASR recharge cycle. Based on injectant and groundwater chemistry and time series water chemistry of recovered water samples during the first ASR operation cycle, initial and evolved hydrochemical facies were evaluated in the Edwards aquifer ASR operation (in New Braunfels). Forward GWB water-water and water-rock interaction modeling revealed the mixing of the injectant and the native groundwater to be the main contributing factor in the hydrochemical facies evolution of groundwater during the first ASR recharge cycle. Estimated hydraulic conductivity values using the numerical PHAST model and corroborated by the Hemker analytical model support the combined effect of lateral flow and vertically-induced flow of high total dissolved solids (TDS) groundwater from the Kainer Formation into the Person Formation via the RDM confining layer during ASR recovery. Estimated hydraulic property values (hydraulic conductivity and porosity) of these three aquifer layers aided in predicting the recovery rate to optimize ASR operations. Implementation of two ASR wells, respectively screened in the Person and Kainer Formations, presents a potential long-term ASR optimization strategy at the Edwards aquifer study site. Induced arsenic releases to concentrations higher than their maximum contaminant level (MCL) of 10 μg/L hinder aquifer storage and recovery (ASR) operations worldwide. Statistical data and time series analyses of the recovered water hydrochemical data were used to assess the operational methodology maintaining the buffer zone for arsenic attenuation during ASR operations in the Floridan aquifer. Additionally, based on Injectant and groundwater hydrochemical data with geochemical data of the aquifer matrix , 1D GWB reactive transport model was used to assess the buffer zone operation methodology that holds promise in managing arsenic releases during ASR operations in the Floridan aquifer. Time series data from the Tampa ASR operations show a positive correlation between percent recovery and arsenic concentration in the recovered water, with high recovery percentages inducing mobilization of arsenic up to 38 μg/L, a value roughly four times the arsenic maximum contaminant level of 10 μg/L. Further, the developed 1D forward reactive transport model suggests underlying processes that control arsenic behavior upon injection of oxygenated source water into a reducing carbonate storage zone. Two model scenarios were used in this study. Model scenario 2 developed such that a larger oxygen front expanded up to 565 m away from the ASR well, three times further than in scenario 1, and promoted the production of Fe(III) oxides/oxyhydroxides with abundances up to 18,700 µg/Kg formed at 555 m away from the ASR well. These Fe(III) oxides/oxyhydroxides may provide sorbing sites that attenuate arsenic concentrations in the groundwater.
Keywords: aquifer storage and recovery; hydraulic parameters; total dissolved solids; arsenic; aquifer quality; storage zone